Differences in perinatal outcomes in teenage mothers with their first and third pregnancies and predictors of adverse neonatal events: A cross-sectional study - Shaymaa Kadhim Jasim; Hayder Al-Momen; Ali Abdul Razzak Obaid (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Repeated teenage pregnancy is a major burden on the healthcare system worldwide. Objective: We aimed to compare teenagers with their first and third pregnancies and to evaluate the likelihood of neonatal complications. Materials and Methods: This cross-sectional study was performed on female teenagers (aged ≤ 19 yr) with singleton pregnancies. The subjects (n = 298) were screened over 12 months. Ninety-six women were excluded, based on the exclusion criteria. The remaining subjects (n = 202) were divided into two groups: teenagers with first pregnancy (n = 96) and teenagers with third pregnancy (n = 47). The subjects were observed throughout pregnancy and delivery. The final sample size of the first and third pregnancy groups was 96 and 47, respectively. Results: There was a significant risk of preeclampsia in the first pregnancy group (p = 0.01). Low birth weight, five-min Apgar score < 7, and neonatal intensive care unit admission were the most significant neonatal outcomes in the first pregnancy group. In the third pregnancy group, significant predictors of neonatal complications included very young age in the first pregnancy ( ≤ 15 yr), an inter-pregnancy interval < 2 yr, current anemia, and history of obstetric and/or neonatal complications in previous pregnancies. Conclusion: Based on the results, teenagers with their first pregnancy had comparable obstetric outcomes (except for preeclampsia) as teenagers with their third pregnancy, whereas neonatal complications occurred more frequently in the first pregnancy group. Overall, we can predict high-risk neonates in the third pregnancy, based on the abovementioned parameters.